PENGARUH KESELAMATAN DAN KESEHATAN KERJA SERTA LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. MALEA ENERGY KABUPATEN TANA TORAJA - Sulu', Agustinus; Chrismesi Pagiu; Lisa Kurniasari Wibisono (MANABIS: Jurnal Manajemen dan Bisnis, 2023)
The purpose of this research is to find out whether safety and health and the work environment affect employee performance. Data collection procedures from this study are: Observation and Questionnaire. The analysis technique uses multiple linear regression tests. The results of the partial test (t test) show that the Occupational Safety and Health and Work Environment variables affect employee performance at PT. Malea Energy, Tana Toraja Regency. Meanwhile, the results of simultaneous testing (F test) show that the Occupational Safety and Health and work environment variables affect employee performance at PT. Malea Energy, Tana Toraja district